Disturbance and recovery in semi‐arid Mediterranean grasslands. Issue 3 (4th December 2012) - Merou, Theodora P.; Tsiftsis, Spyros; Papanastasis, Vasilios P.; O'Connor, Tim
Abstract Aims (1) To investigate the temporal response of semi‐arid Mediterranean grasslands to multiple disturbances as well as P fertilization and irrigation; and (2) to determine the reaction of single species or groups of species as well as the extent of recovery of the grassland community following cessation of the above interventions. Location North Greece. Methods In a fenced area, six treatments (burning, irrigation, digging, cutting, P fertilization and control) were applied, for three growing seasons, in a completely randomized block design with four blocks. Biomass was sampled in five (0.5 × 0.5 m) quadrats per plot at the end of the growing season and sorted into the following functional groups: annual grasses, perennial grasses, annual legumes and forbs (that included all the other species). Measurements were repeated 1 and 7 yr after cessation of the treatments. Results Annual grasses and legumes were positively favoured by cutting, burning and digging, which produced changes in vegetation composition over time. P fertilization had a positive influence on total legume biomass. Effects on individual species were not uniform. Plant composition after cessation of the disturbance treatments was quite different. Total legume biomass remained high 1 yr after the cessation of P fertilization but declined thereafter. Annual grasses and legumes constituted the largest portion of the total biomass in the first year of the experiment. Disturbance (burning, cutting and digging) gradually reduced their biomass in favour of forbs. Seven years after cessation of the treatments, the tall annual, as well as perennial grasses constituted more than 80% of the total biomass. Under conditions of disturbance, short annual species had an advantage over perennials, while cessation of disturbance enables perennial grasses to dominate. Conclusions Disturbance promotes the dominance of annuals, especially species with a persistent seed bank. Repeated disturbance encourages an increase of small or prostrate species. Cessation of disturbance leads to the rapid recovery of biomass production. Tall annuals are promoted. P fertilization clearly favours legumes in the short term.